Prevention And Treatment Of Chronic Energy Deficiency In Pregnant Women: A Scoping Review - Sirajul Munira; Sulistyaningsih Sulistyaningsih; Farida Kartini (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Chronic Energy Deficiency (CED) in pregnant women remains an important maternal health problem, particularly in low- and middle-income settings. CED is associated with inadequate nutritional intake and may contribute to adverse maternal and neonatal outcomes. Therefore, a comprehensive understanding of its determinants, impacts, and management strategies is needed. Methods: This study used a scoping review design guided by the PRISMA-ScR framework and the PCC (Population, Concept, Context) approach. Literature was searched in PubMed, Wiley Online Library, ProQuest, and ScienceDirect for Indonesian- and English-language articles published between 2020 and 2025. The study selection process was conducted using predefined inclusion and exclusion criteria and managed using Rayyan. Of 665 records initially identified, 44 duplicates were removed, and 10 studies were included in the final review. Results: Four major themes were identified: (1) risk factors for CED in pregnant women, including age, socioeconomic conditions, dietary intake, and infectious diseases; (2) the impact of CED on pregnancy and infant health, such as low birth weight, prematurity, and maternal complications; (3) nutritional interventions for CED management, including nutrition education, supplementation, and local food-based supplementary feeding; and (4) prevention strategies through public health policies and community-based support. Conclusion: The evidence indicates that CED in pregnant women is influenced by multidimensional factors and requires integrated prevention and management strategies. Nutrition education, supplementation, local food utilization, and stronger policy implementation are essential to improve maternal nutritional status and pregnancy outcomes.